The economic reconciliation process : Middle Eastern populations in conflict - Bijaoui, Ilan; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
The Economic Reconciliation Process develops hybrid cross-border models based on the free economic zone, the industrial district, and the cluster to generate a common economic interest between countries and populations in declared or potential conflict in the Middle East.
Keywords: Economic development -- Middle East; Peace-building -- Middle East; 0Middle East -- Economic conditions